Effects of oral fatty acid on left ventricular 2-[18F] Fluoro-2-Deoxy-D-Glucose uptake during whole body positron emission and computed tomography - Che Nordin, Mohd Nazmi (2016)
Background: There are two main myocardial metabolic pathways including glucose oxidative pathway and free fatty acid (FFA) oxidative pathway. FFA is the major source of energy for the heart, generating 60% to 90% of energy while glucose metabolism produces the rest 10% to 40% of energy depending on physiological conditions. Objective: This study was carried out to observe the intensity and to analyze the differences in the intensity of 18F-FDG uptake in the wall of LV WITH and WITHOUT oral ingestion of edible oils during whole body (WB) 18F-FDG PET/CT study. Methodology: This is a prospective study involving patients undergoing modified WB 18F-FDG PET/CT protocol; [Group A (n=12) : WB + oral ingestion of 50ml virgin coconut oil (VCO); Group B (n=9) : WB + oral ingestion of 50ml olive oil(OO)]. And Group C (n=9) applied standard preparation protocol for WB 18F-FDG PET/CT examination. The 18FFDG uptake in the wall of LV was qualitatively and quantitatively assessed. Results: The mean age for group A, B, and C were 49.25 ± 13.19, 56.11 ± 11.66 and 64.33 ± 7.50. The mean BMI were 22.46 ± 3.83, 25.68 ± 5.66 and 26.74 ± 4.26 respectively, while the mean FBS were 5.80 ± 1.23, 5.60 ± 1.61 and 5.73 ± 0.51 respectively. The LV uptake of 18F-FDG was significantly higher in Group C patients. There was a significant difference in mean SUVmax at mid (2.58 ± 3.97 vs 2.28 ± 2.75 vs 6.59 ± 2.09, p=0.002), basal (6.43 ± 8.57 vs 4.87 ± 3.08 vs 13.89 ± 3.77, p=0.005) and apical (6.37 ± 8.27 vs 5.33 ± 3.22 vs 11.42 ± 4.66, p=0.002) of LV. The mean normalized 18F-FDG distribution in 20-segment polar map expressed in percentage for Group B was lower in comparison to Group A and Group C (66.37% vs 63.13% vs 68.78%, p=0.04). Conclusion: Oral ingestion of edible oils leads to preference towards fatty metabolism of myocardium hence reduction in glucose uptake.